Substitution of Maize with Cassava and Sweet Potato Meal as the Energy Source in the Rations of Layer Birds - Ayobami Bukola Joseph, Aina; A. O., Fanimo (Universiti Putra Malaysia Press, 1997)
Three hundred and sixty layer hens (36 weeks old Isa Brown) were fed a maize based diet in which sweet potato meal and cassava meal replaced maize in the basal diet during a 12-week trial period. Hen-day egg production was significantly (P< 0.05) depressed lJy cassava meal while birds fed diets with maize and sweet potato meal were not significantly different from each other in hen-day eeg production. Cassava meal significantly reduced (P< O. 05) metabolizable energy intake while there was no significant difference in the crude protein intake of birds fed sweet potato and cassava meal. There was, however, no significant effect from replacing maize with sweet potato or cassava meal on egg, weight, feed intake, shell thickness, Haugh unit, feed/dozen eggs or feed/kg egg (p<0.05). The maize control diet was superior (P< O. 05) in the digestibility of crude protein while energy digestibility was depressed (P< 0.05) with the cassava diet.